Fear, depression, and well-being during COVID-19 in German and South African students: A cross-cultural comparison - Holm-Hadulla, Rainer M.; Mayer, Claude-Hélène; Wendler, Hannes; Kremer, Thomas L.; Kotera, Yasuhiro; Herpertz, Sabine C. (Frontiers in Psychology, 2022)
Various studies have shown a decrease of well-being and an increase in mental health problems during 12 the COVID-19 pandemic; however, only a few studies have explored fear, depression, and well-being 13 cross-culturally during this time. Accordingly, we present the results of a cross-cultural study, taking 14 cultural and contextual aspects into consideration. 15 16 German and South African societies differ from each other socio-culturally, politically and 17 economically. Their university systems also differ to a large extent. This study explores the national 18 differences and similarities between student experiences of fear, depression, and well-being during the 19 pandemic. University students in both countries completed the Fear of COVID-19 Scale, the World 20 Health Organisation-Five Well-Being Index (WHO-5), and the Patient Health Questionnaire-9 (PHQ- 21 9). Welch’s t-test, correlation and multiple regression analyses were performed. German students were 22 found to have statistically lower levels of COVID-19 fear, but higher levels of depression and lower 23 levels of general well-being than South African students. In both samples, fear of COVID was 24 negatively correlated with well-being and positively associated with female gender, while COVID-19 25 fear was positively correlated with depression only in South Africans. Additionally, female gender and 26 lower well-being were identified as predictors of COVID-19 fear in both samples. The findings indicate 27 that the fear of COVID-19 is associated with and varies according to gender and well-being across 28 cultures, and that the difference in the intensity of fear between German and South African students 29 may be partly explained by cultural and contextual differences. 30 31 These findings can create a deeper understanding of the pandemic's impact on student communities 32 and may be used by mental health practitioners and researchers to develop and apply culture-specific 33 interventions.